2013
DOI: 10.1159/000353429
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Children with Growth Hormone Deficiency Treated for Four Years with Growth Hormone Experience Dose-Dependent Increase in Height, but Not in the Rate of Puberty Initiation

Abstract: Background/Aims: Limited data exist on long-term dose response to recombinant human growth hormone (rhGH) in prepubertal GH-deficient (GHD) children. The effect of low, intermediate, and high-dose rhGH (25, 50, and 100 μg/kg/day, respectively) on growth and puberty in children with GHD was investigated for 48 months. Methods: A prospective, dose-response study in 111 patients (aged 3-16 years) evaluated growth velocity (cm/year), height standard deviation score (HSDS), corrected HSDS, bone age/chronologic age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…The analysis of metabolomics provides a powerful tool for determining biomarkers that predict the effects of PEG-rhGH therapy through large-scale molecular analyses. The present study confirmed and extended previous studies by showing the favorable effects of PEG-rhGH therapy on GHD patients ( Rogol et al, 2013 ; Luo et al, 2017 ). To explore the potential mechanism, changes of metabolites of GHD patients in HE and LE groups were monitored using a GC/TOFMS-based metabolomics method.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The analysis of metabolomics provides a powerful tool for determining biomarkers that predict the effects of PEG-rhGH therapy through large-scale molecular analyses. The present study confirmed and extended previous studies by showing the favorable effects of PEG-rhGH therapy on GHD patients ( Rogol et al, 2013 ; Luo et al, 2017 ). To explore the potential mechanism, changes of metabolites of GHD patients in HE and LE groups were monitored using a GC/TOFMS-based metabolomics method.…”
Section: Discussionsupporting
confidence: 91%
“…Growth failure, the primary apparent feature of GHD, may influence the life quality and psychosocial development of affected children ( Chaplin et al, 2015 ; Chinoy and Murray, 2016 ; Leonibus et al, 2016 ). As recorded in recent pharmaceutical studies, recombinant human growth hormone (rhGH) showed a significant therapeutic effect against growth hormone deficiency ( Rogol et al, 2013 ). To achieve this effect, rhGH is required to be administered as a daily injection ( López-Siguero et al, 2011 ; Wit et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study observed a negative correlation between GH dose and pubertal onset but no correlation with treatment duration 124 . In addition, a more recent study that evaluated pubertal onset in 111 GHD children aged 3‐16 years after 48 months of rhGH administration at different doses (25, 50, and 100 µg/kg/day) did not find any significant differences, even if the wide age range of inclusion and lack of control group may bias the findings 125 (Table 1).…”
Section: Growing Up: From Sexual Differentiation To Transition Agementioning
confidence: 97%
“…Limitations of our study included low rhGH doses and high peak serum GH levels in stimulation tests, i. e. patients with peak serum GH levels of up to 9.9 µg/l were included based on a GH cut-off level of 10 µg/l. This is relevant because higher rhGH doses and lower peak GH levels are associated with better response to therapy [2,25]. Moreover, our patient population was small: 81 prepubertal patients and 20 patients already at the onset of puberty (max.…”
Section: Discussionmentioning
confidence: 99%